MicroRNA cluster miR-17–92 Cluster in Exosomes Enhance Neuroplasticity and Functional Recovery After Stroke in Rats. Issue 3 (March 2017) - Xin, Hongqi; Katakowski, Mark; Wang, Fengjie; Qian, Jian-Yong; Liu, Xian Shuang; Ali, Meser M.; Buller, Benjamin; Zhang, Zheng Gang; Chopp, Michael
Abstract : Background and Purpose—: Multipotent mesenchymal stromal cell (MSC) harvested exosomes are hypothesized as the major paracrine effectors of MSCs. In vitro, the miR-17–92 cluster promotes oligodendrogenesis, neurogenesis, and axonal outgrowth. We, therefore, investigated whether the miR-17–92 cluster–enriched exosomes harvested from MSCs transfected with an miR-17–92 cluster plasmid enhance neurological recovery compared with control MSC-derived exosomes. Methods—: Rats subjected to 2 hours of transient middle cerebral artery occlusion were intravenously administered miR-17–92 cluster–enriched exosomes, control MSC exosomes, or liposomes and were euthanized 28 days post–middle cerebral artery occlusion. Histochemistry, immunohistochemistry, and Golgi–Cox staining were used to assess dendritic, axonal, synaptic, and myelin remodeling. Expression of phosphatase and tensin homolog and activation of its downstream proteins, protein kinase B, mechanistic target of rapamycin, and glycogen synthase kinase 3β in the peri-infarct region were measured by means of Western blots. Results—: Compared with the liposome treatment, both exosome treatment groups exhibited significant improvement of functional recovery, but miR-17–92 cluster–enriched exosome treatment had significantly more robust effects on improvement of neurological function and enhancements of oligodendrogenesis, neurogenesis, and neurite remodeling/neuronal dendrite plasticity in the ischemic boundary zone (IBZ) than the control MSC exosome treatment. Moreover, miR-17–92 cluster–enriched exosome treatment substantially inhibited phosphatase and tensin homolog, a validated miR-17–92 cluster target gene, and subsequently increased the phosphorylation of phosphatase and tensin homolog downstream proteins, protein kinase B, mechanistic target of rapamycin, and glycogen synthase kinase 3β compared with control MSC exosome treatment. Conclusions—: Our data suggest that treatment of stroke with tailored exosomes enriched with the miR-17–92 cluster increases neural plasticity and functional recovery after stroke, possibly via targeting phosphatase and tensin homolog to activate the PI3K/protein kinase B/mechanistic target of rapamycin/glycogen synthase kinase 3β signaling pathway. Abstract : Supplemental Digital Content is available in the text.